Pemberdayaan Pengrajin Lulur Timung dalam Akselerasi Kualitas Home SPA Khas Suku Banjar - Mia Fitriana; Khoerul Anwar; Fadlilaturrahmah Fadlilaturrahmah (IKIP PGRI Bojonegoro, 2024)
The traditions of balulur and batimung are still carried out today. One of the production places for cucumber scrub in the city of Banjarmasin is Ipah Zein MSME. The cucumber scrub product by Ipah Zein MSME is a concoction that has been passed down from generation to generation and has been producing cucumber scrub for three generations. During these three generations, the making of scrub and timung was still done traditionally. The quality of this product needs to be improved so that it can still be marketed. The implementation of this service aims to improve the quality dimensions of Ipah Zein MSME timung scrub products, both product quality and packaging quality. Activities will be carried out from April to December 2021 at the Ipah Zein timung scrub production house. The method used begins with preparation, then implementation of activities and evaluation of activities. Activities that have been carried out include modernizing equipment in the production process, assisting production according to Good Cosmetic Manufacturing Practices, mechanizing packaging equipment and improving traditional cosmetic packaging designs. The results show that the service activities have been carried out well, where there has been an increase in the quality of Ipah Zein MSME timung scrub products, both product quality and packaging quality. Service partners have been equipped with knowledge about Good Cosmetic Manufacturing Practices, given equipment that supports this and the product has a more attractive design and is more acceptable to the marketKeywords: scrubs, timung, quality Tradisi balulur dan batimung masih dilakukan sampai saat ini. Salah satu tempat produksi lulur timung di kota Banjarmasin adalah UMKM Ipah Zein. Produk lulur timung oleh UMKM Ipah Zein adalah ramuan warisan turun menurun dan sudah memproduksi lulur timung selama tiga generasi. Selama tiga generasi tersebut, pembuatan lulur dan timung masih dikerjakan secara tradisional. Produk ini perlu ditingkatkan kualitasnya agar tetap dapat dipasarkan. Pelaksanaan pengabdian ini bertujuan untuk meningkatkan dimensi kualitas produk lulur timung UMKM Ipah Zein, baik mutu produk maupun mutu kemasan. Kegiatan dilakukan pada bulan April sampai Desember tahun 2021 di rumah produksi lulur timung Ipah Zein. Metode yang dilakukan diawali dengan persiapan kemudian pelaksanaan kegiatan dan evaluasi kegiatan. Kegiatan yang telah terlaksana meliputi modernisasi peralatan pada proses produksi, pendampingan produksi sesuai Cara Pembuatan Kosmetik yang Baik (CPKB), mekanisasi alat pengemas dan peningkatan desain kemasan kosmetika tradisional. Hasil menunjukkan bahwa kegiatan pengabdian telah terlaksana dengan baik dimana terjadi peningkatan kualitas produk lulur timung UMKM Ipah Zein, baik mutu produk maupun mutu kemasan. Mitra pengabdian telah dibekali pengetahuan mengenai CPKB, diberikan peralatan yang menunjang hal tersebut dan produk telah memiliki desain yang lebih menarik dan lebih dapat diterima pasar.Kata Kunci: lulur, timung, kualitas